(untitled) (Dristikon: A Multidisciplinary Journal, 2021)
Petty trading is such a type of economic activity operating abundance of the low-earning population in new urbanizing developing countries like Nepal. The main aim of this study is to explore factors affecting the household income of petty traders during the COVID-19 Pandemic in Dhahran city. This investigation had used descriptive analysis, and Pearson correlation test to identify the relationship between dependent and independent variables. There were 48 petty traders conveniently selected for the convenient sampling to collect primary data by survey method. The data were analyzed through descriptive statistics by using SPSS. It is found a significant relationship between daily household income and marital status of petty traders. But there was no significant relationship between the daily household income and the size of the family, investment of capital of the petty traders. Similarly, the above results of this study suggest that this study is helpful to the planners and policymakers in Dharan city to formulate suitable policy and manage the micro-business sector including petty traders. And the government should create programs that preserve and establish the economic rights of petty traders and reduce the various complications and taxes which they usually impose on them. The study concluded that there is a significant difference between the household income of petty traders and the marital status of petty traders. Moreover, it established that there was no relationship between the household income and the family size, the investment of capital, and the income before COVID 19 of petty traders.